Adaptive treatment margins to reduce organs at risk dose in patients with no or minimal anatomical changes in radiotherapy of non-small cell lung cancer - Djoya Hattu; Daisy Emans; Janine Bouten; Richard Canters; Judith van Loon; Dirk De Ruysscher (Physics and Imaging in Radiation Oncology)
Background and purpose: In non-small cell lung cancer (NSCLC) a significant portion of the planning target volume (PTV) margin accommodates for anatomical changes during treatment. Patients with no or minimal anatomical changes might therefore benefit from a reduced PTV margin, resulting in lower organ at risk (OAR) doses. We evaluated a plan of the day approach using different PTV margins to quantify its effect on OAR and clinical target volume (CTV) dose. Materials and methods: Twenty NSCLC patients were included in this retrospective study. CBCTs of all fractions were evaluated using an image-guided radiotherapy (IGRT) protocol to classify fractions into two groups: no or minimal anatomical changes to which reduced PTV margin plans (5 or 2 mm) were assigned, or with anatomical changes that received the reference treatment plan (8 mm PTV margin). OAR doses were investigated and CTV coverage was evaluated using CBCT dose recalculations. Results: All plans showed decreased OAR dose when the PTV margin was reduced from 8 mm to 5 mm or 2 mm. The IGRT protocol selected 254/600 fractions in 19/20 patients, that could be treated with a smaller margin. CTV V95% remained ≥95% in 94% of the 5 mm plans and 87% of the 2 mm plans, compared to 98% of the reference 8 mm plans. Conclusion: The IGRT protocol could identify fractions with no or minimal anatomical changes allowing a plan of the day approach to reduce PTV margins. Target coverage remained adequate in the majority of patients, while reducing OAR doses.